Effects of host plant and genetic background on the fitness costs of resistance to Bacillus thuringiensis. - Raymond, B; Wright, D; Bonsall, M (2011)
Novel resistance to pathogens and pesticides is commonly associated with a fitness cost. However, measurements of the fitness costs of insecticide resistance have used diverse methods to control for genetic background and rarely assess the effects of environmental variation. Here, we explored how genetic background interacts with resource quality to affect the expression of the fitness costs associated with resistance. We used a serially backcrossed line of the diamondback moth, Plutella xylostella, resistant to the biopesticide Bacillus thuringiensis, to estimate the costs of resistance for insects feeding on two Brassica species. We found that fitness costs increased on the better-defended Brassica oleracea cultivars. These data were included in two meta-analyses of fitness cost experiments that used standardized protocols (and a common resistant insect stock) but which varied in the methodology used to control for the effects of genetic background. The meta-analysis confirmed that fitness costs were higher on the low-quality host (B. oleracea); and experimental methodology did not influence estimates of fitness costs on that plant species. In contrast, fitness costs were heterogeneous in the Brassica pekinensis studies: fitness costs in genetically homogenized lines were significantly higher than in studies using revertant insects. We hypothesize that fitness modifiers can moderate fitness costs on high-quality plants but may not affect fitness when resource quality is low.